2017
DOI: 10.17509/ijost.v2i2.7995
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Biogenesis Induced by Exercise and Nutrients: Implication for Performance and Health Benefits

Abstract: The skeletal muscle occupies about 40% of body mass, one of the largest organs in the body, and it has great plasticity in response to physiological stressors and then alters the contractile and metabolic properties of the muscles. Therefore, healthy status of muscle affects health status of whole body. Mitochondria are abundantly present in mammalian muscle cells, known as the power plants of the cell to generate adenosine triphosphate (ATP) with oxygen. The muscle health depends on the mitochondrial function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Polyphenol in kedawung acts as an antioxidant that is beneficial for the health of human body by decreasing heart disease attack, hypertension, osteoporosis and cholesterol (Ponnusha et al, 2011;Samruan et al, 2012). (Masuda et al, 2017) also have reported that polyphenols as antioxidants prevent various diseases associated with oxidative stress, such as cardiovascular diseases.…”
Section: Total Phenol Contentmentioning
confidence: 95%
“…Polyphenol in kedawung acts as an antioxidant that is beneficial for the health of human body by decreasing heart disease attack, hypertension, osteoporosis and cholesterol (Ponnusha et al, 2011;Samruan et al, 2012). (Masuda et al, 2017) also have reported that polyphenols as antioxidants prevent various diseases associated with oxidative stress, such as cardiovascular diseases.…”
Section: Total Phenol Contentmentioning
confidence: 95%
“…Nowadays, many sports practitioners such as athletes, trainers, or sports nutrition experts use natural-based ergogenic aids [8]. Our previous studies have revealed that natural plants can be used as ergogenic aids, one of which is curcumin, which can increase mitochondrial biogenesis in skeletal muscle [9][10][11]. In addition, there are also studies on substances contained in natural plants associated with VO 2 Max and LT, such as caffeine, carnitine, and choline at specific doses, which can increase VO 2 max and reduce lactate concentration [12].…”
Section: Introductionmentioning
confidence: 99%
“…Based on our previous studies (Ray et al, 2021a;Ray et al, 2021b;Masuda et al, 2017), here in this study, we have conducted the molecular interaction selected M. fragrans seed constituents as anticancer agents against caspase-3. A docking score was also evaluated for investigating the anticancer activity.…”
Section: Introductionmentioning
confidence: 99%